Numerical Simulation of Failure Characteristics of Reactive Powder Concrete With Steel Fiber - Zhang, Xiaohu; Liu, Songyuan; Li, Gan; Wang, Xiaofei (Frontiers in Physics, 2021)
Steel fibers were delivered into concrete specimens using a mixed congruence method. A coplanar projection method is proposed to solve the problem of discriminating the crossing among steel fibers. Numerical models were built for reactive powder concrete (RPC) cylindrical specimens with 1% and 2% steel fiber. Comparisons between numerical model and actual specimen slices show that the modified method has a good simulation effect. An improved anchor cable unit was used to simulate the bond-slip behavior between steel fiber and concrete; the drawing of a single steel fiber was simulated. Then, the uniaxial compression, triaxial compression, and three-point bending of RPC specimens with 1% steel fiber were simulated, reproducing the concrete cracking and steel fiber slipping behaviors of RPC specimens. The failure modes of numerical RPC specimen under various mechanical tests are consistent with the experimental results, proving the practicability and accuracy of this established numerical model. This study provides a foundation for the numerical simulation of RPC properties.